Analysis of sculling propulsion mechanism using two-components particle image velocimetry - Kamata, E.; Miwa, T.; Matsuuchi, K.; Shintani, H.; Nomura, T. (Biomechanics and Medicine in Swimming X, 2006)
The flow field around a human body during swimming presents a very unsteady condition. This study analyzed the flow field around the hand using particle image velocimetry method. A male subject participated in this study, and the flow field around the hand during the sculling motion was visualized. The results indicate that a pair of vortices and the jet flow occurs around hand during sculling motion. The swimmer generated a great propulsive force as a reaction force of the jet flow. The theoretical value of the jet flow of a vortex ring and the experimental value were indicated as nearly equal. This measurement is expected to become an index for evaluating propulsive force in unsteady conditions.